Kundalini yoga as mutual recovery: a feasibility study including children in care and their carers - Perez, Elvira; Ball, Mark; Brown, Poppy; Crepaz-Keay, David; Haslam-Jones, Emily; Crawford, Paul (Emerald, 2016)
This is a mixed-methods feasibility study to test whether incorporating a 20-week Kundalini yoga program into a children’s home community improves wellbeing outcomes. Feasibility was assessed through recruitment and retention rates as well as participants’ self-report perceptions on social inclusion, mental health, wellbeing and semi-structured interviews on the benefits of the study. Mutual recovery entailed that children in care (CiC), youth practitioners, and management participated together in the kundalini yoga sessions. The study initially enrolled 100% of CIC and 97% (29/30) of eligible staff. Attendance was low with an average rate of four sessions per participant (Std. D 3.7, range 0-13). All the participants reported that the study was personally meaningful and experienced both individual (e.g., feeling more relaxed) and social benefits (e.g., feeling more open and positive). Pre- and post- yoga questionnaires did not show any significant effects. Low attendance was associated with the challenges faced by the children’s workforce (e.g., high levels of stress, low status, profile, and pay) and insufficient consultation and early involvement of stakeholders on the study implementation process. This study has generated a number of valuable guiding principles and recommendations that might underpin the development of any future intervention for CIC and staff working in children’s homes.